2021
DOI: 10.3847/1538-4357/abee68
|View full text |Cite
|
Sign up to set email alerts
|

I Spy Transits and Pulsations: Empirical Variability in White Dwarfs Using Gaia and the Zwicky Transient Facility

Abstract: We present a novel method to detect variable astrophysical objects and transient phenomena using anomalous excess scatter in repeated measurements from public catalogs of Gaia DR2 and Zwicky Transient Facility (ZTF) DR3 photometry. We first provide a generalized, all-sky proxy for variability using only Gaia DR2 photometry, calibrated to white dwarf stars. To ensure more robust candidate detection, we further employ a method combining Gaia with ZTF photometry and alerts. To demonstrate its efficacy, we apply t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
91
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 90 publications
0
91
0
Order By: Relevance
“…Though the two metrics are based on different data sets, if they are both capable of identifying genuine variable Gaia sources, there should be a significant overlap in the samples of variable candidates selected using them. We find that about half of the top 1 per cent variable white dwarf candidates within 200 pc selected by Guidry et al (2021) also have EXCESS FLUX ERROR >4. Additionally all eight new ZZ Ceti that Guidry et al (2021) identified using their Gaia variability index have EXCESS FLUX ERROR >4.6.…”
Section: A N I N D I C Ato R O F I N T R I N S I C Va R I a B I L I T Ymentioning
confidence: 73%
See 2 more Smart Citations
“…Though the two metrics are based on different data sets, if they are both capable of identifying genuine variable Gaia sources, there should be a significant overlap in the samples of variable candidates selected using them. We find that about half of the top 1 per cent variable white dwarf candidates within 200 pc selected by Guidry et al (2021) also have EXCESS FLUX ERROR >4. Additionally all eight new ZZ Ceti that Guidry et al (2021) identified using their Gaia variability index have EXCESS FLUX ERROR >4.6.…”
Section: A N I N D I C Ato R O F I N T R I N S I C Va R I a B I L I T Ymentioning
confidence: 73%
“…We find that about half of the top 1 per cent variable white dwarf candidates within 200 pc selected by Guidry et al (2021) also have EXCESS FLUX ERROR >4. Additionally all eight new ZZ Ceti that Guidry et al (2021) identified using their Gaia variability index have EXCESS FLUX ERROR >4.6.…”
Section: A N I N D I C Ato R O F I N T R I N S I C Va R I a B I L I T Ymentioning
confidence: 73%
See 1 more Smart Citation
“…The observational evidence of planetary systems around white dwarfs is abundant (Zuckerman & Becklin 1987;Graham et al 1990;Aannestad et al 1993;Vanderburg et al 2015;Gänsicke et al 2019;Manser et al 2019;Vanderbosch et al 2020;Vanderburg et al 2020;Guidry et al 2021;Vanderbosch et al 2021). To date, the majority of detections of planetary material at white dwarfs have come from identifying pollutant metals in their atmospheres -the result of ac-white dwarf ( 1 R ).…”
Section: Introductionmentioning
confidence: 99%
“…Additional observational evidence comes from the presence of gas discs within the circumstellar dust discs (Gänsicke et al 2006;Farihi et al 2012;Melis et al 2012;Gentile Fusillo et al 2021), which may be related to the presence of intact solid planetesimals embedded within some of the dusty debris discs (Manser et al 2019). The fundamental hypothesis of planetesimals reaching the tidal disruption radius (Jura 2003) has unambiguously been corroborated by the detection of two systems exhibiting deep and rapidly evolving photometric transits caused by disintegrating planetary bodies (Vanderburg et al 2015;Vanderbosch et al 2019;Guidry et al 2021;Vanderbosch et al 2021). More recently this body of evidence has come to include bona fide planets orbiting close to the white dwarf -in one case detection of an evaporating giant planet (Gänsicke et al 2019) and another from photometric transits of a planet crossing the line-of-sight of the white dwarf (Vanderburg et al 2020).…”
Section: Introductionmentioning
confidence: 96%